2016
DOI: 10.1136/emermed-2015-204841
|View full text |Cite
|
Sign up to set email alerts
|

‘You're never making just one decision’: exploring the lived experiences of ambulance Emergency Operations Centre personnel

Abstract: Background The aim of this study was to explore the experiences of ambulance dispatch

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(89 citation statements)
references
References 34 publications
5
84
0
Order By: Relevance
“…In a recent study,Hegg-Deloye et al, (2014, p. 247) reviewing the current state of literature concluded that paramedics accumulate a set of risk factors, including acute and chronic stress, that can lead to the development of cardiovascular diseases and "post-traumatic disorders, sleep problems and obesity are prevalent among paramedics. "Coxon et al, (2016) has found similar evidence of key stressors and their impact on well-being of staff working in the ambulance dispatch. Halpern et al, (2011, p.51) similarly argued that ambulance workers frequently deal with stressful or critical incidents that can result in significant 'emotional sequelae', such as depression, burnout and post-traumatic stress symptoms.Sickness absence data in the UK NHS has been published by the Department of Health(DH) and Office for National statistics (ONS).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In a recent study,Hegg-Deloye et al, (2014, p. 247) reviewing the current state of literature concluded that paramedics accumulate a set of risk factors, including acute and chronic stress, that can lead to the development of cardiovascular diseases and "post-traumatic disorders, sleep problems and obesity are prevalent among paramedics. "Coxon et al, (2016) has found similar evidence of key stressors and their impact on well-being of staff working in the ambulance dispatch. Halpern et al, (2011, p.51) similarly argued that ambulance workers frequently deal with stressful or critical incidents that can result in significant 'emotional sequelae', such as depression, burnout and post-traumatic stress symptoms.Sickness absence data in the UK NHS has been published by the Department of Health(DH) and Office for National statistics (ONS).…”
mentioning
confidence: 74%
“…Living a life on the edge (Hewitt and Luce, 2006) has its own perverse consequences. There is a growing discourse surrounding the various health related issues in the ambulance service with the underlying assumption that such work is inherently stressful (Hegg-Deloye et al, 2014;Coxon et al, 2016;Mishra et al, 2010;Sterud, et al, 2011Sterud, et al, , 2006Sterud, et al, , 2008Bennett et al, 2004;Pajonk, et al, 2011;Nightingale andMark, 1988, Clohessy andEhlers, 1999;Alexander and Klein, 2001;Mahony, 2001). To this effect, Sterud et al, (2011, p.2) argue that ambulance personnel routinely attend non-emergency work, such as transporting and providing appropriate care to chronically and terminally ill patients, which imposes "different emotional demands and which might be experienced as more emotionally exhausting than more sensational events".…”
Section: Implication Of Work Intensity On Sickness Absence In the Ambmentioning
confidence: 99%
“…Studies were conducted in a range of countries; seven were from the USA ( Doerner, 1987 ; Jenkins, 1997 ; Tracy & Tracy, 1998 ; Shuler & Sypher, 2000 ; Pierce & Lilly, 2012 ; Anshel, Umscheid & Brinthaupt, 2013 ; Palmer, 2014 ), four were from the UK ( James & Wright, 1991 ; Wastell & Newman, 1996 ; Sprigg, Armitage & Hollis, 2007 ; Coxon et al, 2016 ), two from Australia ( Shakespeare-Finch, Rees & Armstrong, 2014 ; Adams, Shakespeare-Finch & Armstrong, 2015 ), one from France ( Weibel et al, 2003 ), one from Sweden ( Forslund, Kihlgren & Kihlgren, 2004 ), and one from Ireland ( Gallagher & McGilloway, 2008 ). Populations studied included operatives across different emergency services; eight studied ambulance EDC operatives ( James & Wright, 1991 ; Wastell & Newman, 1996 ; Weibel et al, 2003 ; Sprigg, Armitage & Hollis, 2007 ; Gallagher & McGilloway, 2008 ; Shakespeare-Finch, Rees & Armstrong, 2014 ; Adams, Shakespeare-Finch & Armstrong, 2015 ; Coxon et al, 2016 ), one studied fire EDC operatives ( Palmer, 2014 ), and five studied police EDC operatives ( Doerner, 1987 ; Tracy & Tracy, 1998 ; Shuler & Sypher, 2000 ; Pierce & Lilly, 2012 ; Anshel, Umscheid & Brinthaupt, 2013 ). In one study EDC operatives handled fire and ambulance calls ( Jenkins, 1997 ), and in one study EDC operatives handled fire, police, and ambulance calls ( Forslund, Kihlgren & Kihlgren, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Third, communicating with anyone who might act as a vessel for emotions that might overcome ambulance personnel following the event aids in internalizing the stressful experience and assists in coping with tough memories. [10][11][12] Chronic work stress among EMS personnel has been associated with burnout, decreased job satisfaction, fatigue, impaired physical health, higher percentages of job turnover, and significant posttraumatic stress symptomatology. 13,14 Our hypothesis was that there is a correlation between burnout vs sociodemographic characteristics and work-related factors and coping methods of EMS professionals.…”
Section: Introductionmentioning
confidence: 99%